2018
DOI: 10.1021/acs.orglett.7b03930
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ring Ortho Substituents on the Configuration of Carotenoid Polyene Chains

Abstract: The 9-(Z)-configuration was exclusively obtained in the carotenoid polyene chain irrespective of olefination and disconnection methods for terminal ortho-unsubstituted benzene rings. The 2,6-dimethyl substituents in the terminal rings secure an all-(E)-polyene structure. The single molecular conductance of the pure 9-(Z)-carotene was measured for the first time to be 1.53 × 10 ± 6.37 × 10G, whose value was 47% that of the all-(E)-carotene ((3.23 × 10) ± (1.23 × 10) G).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The first group (Table , entries 1–3) demonstrated the strongest antioxidant activities, which showed the structural features of ortho - and multiple electron-donating substituents in the aromatic rings. It suggested that ortho -substitution induced more to the all- E configuration of the polyene chain . The second-best group in radical scavenging activity contained an electron-donating substituent at the para -position of the aromatic ring, which favored 9′- Z configuration of the carotenoid polyene chain (Table , entries 4, 5, 7, and 8).…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…The first group (Table , entries 1–3) demonstrated the strongest antioxidant activities, which showed the structural features of ortho - and multiple electron-donating substituents in the aromatic rings. It suggested that ortho -substitution induced more to the all- E configuration of the polyene chain . The second-best group in radical scavenging activity contained an electron-donating substituent at the para -position of the aromatic ring, which favored 9′- Z configuration of the carotenoid polyene chain (Table , entries 4, 5, 7, and 8).…”
mentioning
confidence: 91%
“…The configuration of the polyene chain was carefully assigned to be either all- E or 9′- Z , or a mixture of both by comparing their 1 H NMR spectra with those of all-( E )-carotene 1b and 9′-( Z )-carotene 1g (Table ). , The numbering sequence followed the carotenoid tradition, instead of the systematic IUPAC rule …”
mentioning
confidence: 99%
See 3 more Smart Citations